Molecular studies of stiff skin-causing mutations in fibrillin-1 - Iqbal, S (2011)
Fibrillin-1 is the main component of the 10-12 nm microfibrils, which are found in several elastic and non-elastic tissues. Human fibrillin-1 contains multiple calcium-binding epidermal growth factor-like (cbEGF) domains interspersed with transforming growth factor β-binding protein-like (TB) domains. TB4 domain contains a flexible RGD loop which mediates cell adhesion via αVβ3, α5β1 and αVβ6 integrins. Mutations which introduce amino acid substitutions into TB4 are associated with a wide spectrum of diseases such as Marfan syndrome (MFS), ectopia lentis, Stiff skin syndrome (SSS). Amino acid substitutions such as W1570C, C1564S and C1577G in the TB4 domain have been found to cause SSS. The upstream TB5 domain has been predicted to modulate integrin binding and a deletion in the domain has been found in Weill-Marchesani syndrome (WMS), phenotype of which is similar to SSS (skin fibrosis and short stature), thereby suggesting that the underlying pathogenic mechanism might be similar. This study has used cellular, biochemical and biophysical methods to investigate the effects of SSS substitutions C1564S and W1570C on domain structure and function and compared it to a MFS substitution C1564Y in the TB4 domain and WMS deletion in the TB5 domain. Effects of the SSS mutations on structure of the domains were studied using limited proteolysis, nuclear magnetic resonance spectroscopy and calcium chelation experiments. Subsequently, the ability of human fibroblasts to secrete wild-type and mutant fibrillin-1 was examined to identify the effect of the mutations on the trafficking of the protein. Finally, cell binding assays and SPR was employed to investigate the effect of disease-causing mutations on fibrillin-1/integrin interactions. The results demonstrate that the SSS mutations affect TB4-cbEGF23 interface and calcium-binding to cbEGF23 but do not alter secretion of recombinant fibrillin-1 mutant fragments from the cell. On the other hand, intracellular retention was observed for MFS substitution C1564Y which was shown to be more susceptible to proteolysis than SSS substitution C1564S. WMS deletion also gives rise to partial retention of the recombinant fragment, suggesting a different pathogenic mechanism for these disorders. Cell binding assays and surface plasmon resonance (SPR) experiments show that SSS mutations affect binding to αvβ3 integrin, but not αvβ6 integrin suggesting that selectively impaired integrin interactions may contribute to pathogenesis of SSS.